2020
DOI: 10.29252/ijop.14.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Integrated All-Optical Analog to Digital Converter

Abstract: We present the procedure for designing a high speed and low power alloptical analog to digital converter (AO-ADC), by integrating InGaAsP semiconductor optical amplifier (SOA) with InP based photonic crystal (PhC) drop filters. The self-phase modulation in the SOA can shift the frequency of the Gaussian input pulse. The two output PhC based drop filters are designed to appropriately code the frequency-shifted analog signals by the SOA, converting them to four desired digital output levels. Our numerical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…However, this is not the major aim of this proposal. As expected, the PhC-SOA SPM incurs a redshift on the output pulse signal that increases linearly with an increase in the input pulse bandwidth (∆λ1/2) for different values of ng, similar to conventional SOA (Moshfe et al 2020). As shown in Fig.…”
Section: Phc-soa Designsupporting
confidence: 76%
See 4 more Smart Citations
“…However, this is not the major aim of this proposal. As expected, the PhC-SOA SPM incurs a redshift on the output pulse signal that increases linearly with an increase in the input pulse bandwidth (∆λ1/2) for different values of ng, similar to conventional SOA (Moshfe et al 2020). As shown in Fig.…”
Section: Phc-soa Designsupporting
confidence: 76%
“…The signal gain and the frequency chirp in the pulse signal of a PhC-SOA, while compared with those in a conventional SOA, have been discussed in (Nosratpour et al 2018). It has already been shown that in PhC-SOA, for an input temporal pulse of width p, the larger the signal gain of the amplifying cavity, the larger the shift in the wavelength of the chirped signal (∆λout) (Nosratpour et al 2018), similar to what examined in conventional SOAs (Moshfe et al 2020). However, in PhC-SOA the wavelength shift depends on the group index too.…”
Section: Numerical Modelmentioning
confidence: 69%
See 3 more Smart Citations